Reação do mercado em fusões & aquisições Cross-border de firmas brasileiras - Takenouchi, Pedro Issao (2012)
The primary objective of this study is to examine the market reaction to cross-border acquisitions of Brazilian multinational emerging-companies (MECs). On this purpose, we examine 128 mergers and acquisitions announcements associated with 36 (MECs) during the sample period 2000 2011. The mergers and acquisitions announcements data come from the Thomson SDC Platinum database. On this dissertation was employed the event study methodology to measure the impact of the announcements on the value of acquiring firms. Herein were established as windows event, 11, 15 and 5 days; furthermore, as windows estimation, were adopted 120, 240 and 500 days. Resulting in a total of 1,140 analysis of merger and acquisition from the original sample. Thus, the results show that, on average, cross-border acquisitions of MECs do not create value to the acquirers. Moreover, in order to explore the influencing factors of the direction and magnitude of market reaction; herein, were deeply analyzed some explanatory variables based on Resource-based View (RBV) and the cross border acquisitions literature, through stratifying event studies results, applying ordinary least square regression, and besides, a non parametric statistical analysis; yclept, bootstrap. Thereby, the empirical findings provide evidence that economic distance, acquisitions on developed countries, past performance, firm size, periods of crises and recessions, serial acquirers, among others variables; as performance drivers for Brazilian s (MECs) cross-border acquisition